In vitro anidulafungin activity against yeasts – system and disseminated mycosis pathogens - A. B. Kulko (Онкогематология)
We analyzed susceptibility to anidulafungin of yeasts clinical strains of Candida (14 species), Cryptococcus (1 species), Geotrichum (1 species), Rhodotorula (1 species) and Saccharomyces (1 species). We revealed high anidulafungin activity against Candida spp., both common species and rare pathogens of candidiasis. It was found that over 99 % of Candida strains do not have an acquired resistance mechanisms to anidulafungin (microbiological criteria). The anidulafungin is not active against strains of Cryptococcus neoformans and Rhodotorula mucilaginosa.